Post-acquisition integration and growth of farms: The case of Ukrainian agroholdings - Igor Ostapchuk; Taras Gagalyuk; Jarmila Curtiss (International Food and Agribusiness Management Review, 2021)
This paper presents a dynamic perspective on the processes of farm restructuring following farm acquisitions by large-scale agroholdings in Ukraine. In particular, the paper employs a large dataset of farm-level data and several quantitative techniques to explore how the acquired farms' resource bases are integrated after acquisitions and what outcomes an acquisition brings about for farm growth, profitability and productivity. In general, acquisitions positively affect farm growth and productivity while agroholdings use various resource allocation, resource redeployment and investment/divestment instruments for the post-acquisition integration of farms. The variation in achieving profitable post-acquisition growth of farms is contingent upon a number of farm pre-acquisition characteristics, strategic growth orientations and timing of acquisitions.
Keywords: G34; L25; Q14; 330; acquisition waves; agroholdings; farm growth; post-acquisition integration; Ukraine